Penerapan Metode Forward Chaining Pada Aplikasi Daring Untuk Mendeteksi Penyakit Anemia - Endah Budiyati; Erni Rihyanti (STMIK Budi Darma, 2022)
An important factor in carrying out daily activities is the fulfillment of good health conditions. Many people do not care about the condition of the body so that it can affect health where in the end the disease will easily come to cause conditions that threaten the body to death. This indifference is due to being late in anticipating the situation so that it is often handled too late. Anemia is one of the diseases that often come unnoticed by the community where if it is handled too late, it will be life-threatening. Symptoms of anemia suffered by the community are usually treated by going to the puskesmas for examination. Examinations carried out by visiting the puskesmas certainly take time and energy where not all people have free time. Overcoming this, this research can help the community to find solutions quickly and effectively when health conditions occur and treat anemia symptoms. The experimental method in this type of qualitative research is the choice in the current research. Data analysis was conducted to collect data by interviewing sources of information related to the research material. The system development method applied uses the waterfall model where each stage of development is carried out gradually downwards. The system development is then implemented in the form of a web-based system using PHP programming and MySQL as the database. The technical language of the system development itself uses UML tools such as activity diagrams, use case diagrams, sequence diagrams. This research produces an application in the form of an expert information system to detect anemia based on references from experts using the Forfard Chaining Method. The Forward Cahining method is a forward reasoning method that uses facts as knowledge representations to draw conclusions. This developed system produces output in the form of a diagnosis calculation for the user whether he is suffering from anemia or not.